Relevance Theory in Literature: Inferential Analysis of Audre Lorde’s Poem ‘From the House of Yemanjá’ - Ei Mon Kyaw (English Language Education Study Program, Faculty of Social, Economics, and Humanities, University of Nahdlatul Ulama Purwokerto, 2023)
In order to perform an inferential analysis using a relevance theory, this study pragmatically analyzes the poetry